Simulasi Numerik Gelombang Tinggi di Sulawesi Utara Saat Terjadi Siklon Tropis Kimi Menggunakan Model Gelombang SWAN - Andariwan, Yogi Muhammad; Ningsih, Nining Sari; Kartadikaria, Aditya Rakhmat (Jurnal Meteorologi dan Geofisika, 2024)
This study investigates wind and wind wave conditions in North Sulawesi waters based on their climatological characteristics and a case study of when high waves occurred during Tropical Cyclone (TC) Kimi. Climatological characteristics are calculated by using ERA5 data and the case study is conducted by simulation using Simulating Waves Nearshore (SWAN) wave model. Model verification was performed by comparing the significant wave height (SWH) from SWAN with observation data from wave buoys in Albatross Bay, Townsville, and Emu Park. The statistical results provide biases of -0.11 m, 0.22 m, and 0.16 m, respectively. The Root Mean Square Error (RMSE) values are 0.14 m, 0.28 m, and 0.23 m, and the correlation coefficients are 0.54, 0.8, and 0.95. During the December- February (DJF) period, wind speed peaks in February (3.0-6.5 m/s), and the SWH reaches 0.5-0.8 m. On 17th of January 2021, Manado's coastline experienced high waves, coinciding with the active phase of TC Kimi near northeastern Australia from 15th to 19th of January 2021. As TC Kimi developed, wind speeds in North Sulawesi increased to 7.0–12 m/s, triggering waves reaching 1.0–1.8 meters with an anomaly of 1–1.5 meters. This wave activity experienced a time lag of +19 hours in response to the wind speeds generated by TC Kimi.